Management of Facilities and Infrastructure in Improving the Quality of Learning in Madrasah Tsanawiyah Ibnu Sina Karawang - Sonia Yulianti; Abubakar Umar (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
In the implementation of learning and education, facilities and infrastructure are very important. The existence of management of facilities and infrastructure in educational institutions will be maintained and its use clear. If the existing facilities and infrastructure are inadequate, the implementation of the learning process in schools can be hampered and not run well. Vice versa, if the facilities and infrastructure are complete and supportive, they will be able to facilitate the learning process, because complete facilities and infrastructure will provide variations in the learning process. This study aims to determine how the management of facilities and infrastructure in improving the quality of learning at the Madrasah Tsanawiyah Ibnu Sina Karawang. It is carried out with a qualitative descriptive approach which is carried out by analyzing, describing, and summarizing various conditions obtained from a collection of information obtained from field interviews or direct observations regarding the problem in question. In managing facilities and infrastructure, MTs Ibnu Sina Karawang has implemented planning, procurement, and management of facilities and infrastructure. However, the condition of the facilities and infrastructure at MTs Ibnu Sina Karawang is still very minimal, with the condition of the rooms being lightly damaged and some heavily damaged, there is a leaky classroom roof, there is no library and laboratory space and the condition of the benches and tables are damaged. This is because there are still limited funds and budgets, and the number of students can be considered quite small. the existing funds are not sufficient to cover the costs in the management of facilities and infrastructure.